Surfing on Membrane Waves: Microvilli, Curved Membranes, and Immune Signaling - Orbach, Ron; Su, Xiaolei (Frontiers in Immunology, 2020)
Microvilli are finger-like membrane protrusions supported by the actin cytoskeleton and found on almost all cells. A growing body of evidence suggests that the dynamic lymphocyte microvilli, with their unique structural properties, play an important role in signal transduction leading to immune responses. Nevertheless, challenges in modulating local membrane curvature and monitoring the high membrane dynamicity of microvilli hampered the investigation of the curvature-generation mechanism and its functional consequences in signaling. These technical barriers have been partially overcome by recent advancements in adapted super-resolution microscopy and high-precision nanofabrication technology. Here, we review the up-to-date progress in understanding the mechanisms and functional consequences of microvilli in lymphocyte signaling. We discuss how the deformation of local membranes affects the organization of signaling proteins and their biochemical activities. We propose that curved membranes, together with the underlying cytoskeleton, shape microvilli into a unique compartment that sense and process signals leading to lymphocyte activation.